Kesejahteraan Ekonomi Pengemudi Ojek Online dalam Aspek Pendapatan, Tabungan, dan Investasi - Kurniawan, Yohanes Jhony; Julianto , Heppy; Suhartono, Suhartono (J-CEKI : Jurnal Cendekia Ilmiah, 2026)
The welfare of online motorcycle taxi drivers is currently facing economic uncertainty and a downward trend in daily income. The goal of this study is to evaluate the association between income level and saving behavior in online drivers, to evaluate the relationship between income level and investment behavior, and to determine additional factors that influence the financial behavior of motorcycle taxi drivers in Indonesia. This investigation uses a descriptive quantitative method. The conclusions are; There is a substantial association between online motorcycle taxi drivers' income and saving habit, There is a substantial association between online motorcycle taxi drivers' income and investment behavior, and There is a considerable relationship between online motorcycle taxi drivers' income and external and internal characteristics.